Fernando García de la Vega an essential on TVE - Carreras Lario, Natividad Cristina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Fernando García de la Vega was one of the professionals who launched television in our country. the professionals were true pioneers, inventing formats, imagining content while learning to use the new television technology, and experimenting with the new audiovisual. García de la Vega began doing all kinds of programs, specializing in contests and musicals. he is one of the first and great masters of Spanish television. this work focuses on some of the most emblematic programs that he created, scripted, directed and produced.